Physical Activity During Pregnancy and Language Development in the Offspring. Issue 3 (10th April 2013) - Jukic, Anne Marie Z.; Lawlor, Debbie A.; Juhl, Mette; Owe, Katrine M.; Lewis, Barbara; Liu, Jihong; Wilcox, Allen J.; Longnecker, Matthew P.
Abstract Background In rodents, physical activity during pregnancy has been associated with improved learning and memory in the offspring. We used data from the Avon Longitudinal Study of Parents and Children (born in 1991–92) to investigate maternal physical activity during pregnancy and offspring language development. Methods At 18 weeks of gestation, women reported the hours per week they participated in 11 leisure‐time physical activities and the hours per week spent in general physical activity (leisure, household and occupational). Caregivers completed a modified MacArthur Infant Communication scale at 15 months. Verbal intelligence quotient (IQ) was measured at age 8 years. Regression analysis was used to examine the associations of physical activity with MacArthur score (more than 75th percentile) and verbal IQ. The number of participants available for analyses ranged from 4529 to 7162. Results Children of women in the two highest quintiles of leisure activity (compared with no leisure activity) were more likely to have high 15‐month MacArthur scores (adjusted odds ratio 1.2 [95% confidence interval 0.9, 1.4] and adjusted odds ratio 1.4 [95% CI 1.1, 1.7], respectively). Leisure activity was not associated with IQ, while general physical activity was linked with lower verbal IQ (1 and 3 points lower for the two highest quintiles). Conclusions The most robust finding was a transient increase in offspring vocabulary score at young ages with maternal leisure activity. Differences in the associations with leisure‐time physical activity compared with general physical activity need further exploration.